Utility of cone unit liver resection for small hepatocellular carcinoma: a propensity score matched analysis. Issue 5 (May 2021) - Imura, Satoru; Yamada, Shinichiro; Saito, Yu; Ikemoto, Tetsuya; Morine, Yuji; Shimada, Mitsuo
Abstract: Background: Anatomical resection (AR) is performed widely for hepatocellular carcinoma (HCC). However, it is controversial whether typical AR, which removes the whole feeding territory of the tumor-bearing portal branch bordered by the landmark veins, is necessary. The aim of this study was to investigate the utility of small AR, so-called cone unit resection, for small HCC. Methods: Between 2007 and 2019, 372 hepatectomies were performed for HCC. Among them, 91 initial resections for small (<5 cm) solitary HCC were performed by typical AR (n = 44) or cone unit AR (n = 47). Propensity score matching was performed and clinicopathological features including prognosis were compared. Results: At baseline, platelet count was higher, and liver function (serum albumin level) and indocyanine green retention at 15 min were better in the typical AR than cone unit AR group. There was no significant difference between the typical AR and cone unit AR group for tumor characteristics, short- and long-term outcomes. Even after propensity score matching (n = 29), the short- and long-term outcomes were also equivalent in between the two groups. Conclusion: There was no difference in prognosis of typical and cone unit AR. Therefore, cone unit AR is a feasible procedure for small HCC.